Dynamic Changes in Arabinogalactan-Protein, Pectin, Xyloglucan and Xylan Composition of the Cell Wall During Microspore Embryogenesis in Brassica napus - Corral-Martínez, Patricia; Driouich, Azeddine; Seguí-Simarro, Jose M. (Frontiers in Plant Science, 2019)
Microspore embryogenesis is a manifestation of plant cell totipotency whereby new cell walls are formed as a consequence of the embryogenic switch. In particular, the callose-rich subintinal layer created immediately upon induction of embryogenesis was recently related to protection against stress. However, little is currently known about the functional significance of other compositional changes undergone by the walls of embryogenic microspores. We characterized these changes in Brassica napus at different stages during induction of embryogenic microspores and development of microspore-derived embryos (MDEs) by using a series of monoclonal antibodies specific for cell wall components, including arabinogalactan-proteins (AGPs), pectins, xyloglucan and xylan. We used JIM13, JIM8, JIM14 and JIM16 for AGPs, CCRC-M13, LM5, LM6, JIM7, JIM5 and LM7 for pectins, CCRC-M1 and LM15 for xyloglucan, and LM11 for xylan. By transmission electron microscopy and quantification of immunogold labeling on high-pressure frozen, freeze-substituted samples, we profiled the changes in cell wall ultrastructure and composition at the different stages of microspore embryogenesis. As a reference to compare with, we also studied in vivo microspores and maturing pollen grains. We showed that the cell wall of embryogenic microspores is a highly dynamic structure whose architecture, arrangement and composition changes dramatically as microspores undergo embryogenesis and then transform into MDEs. Upon induction, the composition of the preexisting microspore intine walls is remodeled, and unusual walls with a unique structure and composition are formed. Changes in AGP composition were related to developmental fate. In particular, AGPs containing the JIM13 epitope were massively excreted into the cell apoplast, and appeared associated to cell totipotency. According to the ultrastructure and the pectin and xyloglucan composition of these walls, we deduced that commitment to embryogenesis induces the formation of fragile, plastic and deformable cell walls, which allow for cell expansion and microspore growth. We also showed that these special walls are transient, since cell wall composition in microspore-derived embryos was completely different. Thus, once adopted the embryogenic developmental pathway and far from the effects of heat shock exposure, cell wall biosynthesis would approach the structure, composition and properties of conventional cell walls.